The Effect of Students’ Activeness in Vocabulary Building Program Toward The English Vocabulary Achievement - Lus Firdaus Zakiya (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study was conducted in the tenth grade of Harapan Ummat High School. This study aims to determine the effect of students’ activeness in vocabulary building program toward the English vocabulary achievement of the tenth grade students at SMA Unggulan Harapan Ummat. This study used quantitative research method with Ex-post facto design. The population used in this study were 41 tenth grade students. The data collection techniques used were tests (multiple choice) and documentation. Testing the results of this study using SPSS 27 for windows. This research hypothesis test uses simple linear regression analysis. The results showed that there was an impact of student activeness in the vocabulary building program on the results of English grades at Harapan Ummat Unggulan High School with a percentage of 27% with an R-count of 0.522. These results indicate that there is a positive impact of student activeness then 73% shows other impacts that are not examined by researchers.